Printed visual materials for flood awareness and preparedness using participatory graphic design the case of the SHS students of Mangagoy National High School - Feliscuzo, Quincy B.; Cayamanda, Karen Joyce G. (2023)
Traditionally, disaster management agencies have relied on printed materials as a primary means of one-way communication to educate individuals about natural hazards and the risks they pose. However, this approach often limits the effectiveness of communication, as it fails to actively engage and involve the target audience. The use of static and generic materials may not effectively capture the attention or resonate with individuals, leading to reduced awareness and preparedness levels. ?This study rolled-out a phenomenological qualitative approach in data collection and analysis through interviews viewed from the lens of participatory communication principles and the stages of participatory design. Graphic design process was also utilized as the medium for the design of the print materials. The analysis and interpretation of results show that participatory design can be used to effectively disseminate flood awareness and preparedness messages to local audiences. The results revealed that print materials for disaster management can be created through a localized and participatory approach in voicing out the flood narratives of the stakeholders involved, positioning them as the center of visual design and print material creation. Thus, the proposed participatory graphic design is a derivative of the Participatory Design methodology. Among the recommendations is the development of an action plan to maximize the impact of the student designed posters and ensure the effective communication of flood related messages. The study calls for future participatory design studies to explore various dimensions, impact assessment, evaluation strategies, and provide recommendations on improving communication and community engagement.
Thesis (BA Communication and Media Arts) --University of the Philippines Mindanao, 2023